2021
DOI: 10.1094/phyto-08-20-0358-fi
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Adaptation of Forest and Crop Pathogens in the Anthropocene

Abstract: Anthropocene marks the era when human activity is making a significant impact on earth, its ecological and biogeographical systems. The domestication and intensification of agricultural and forest production systems have had a large impact on plant and tree health. Some pathogens benefitted from these human activities and have evolved and adapted in response to the expansion of crop and forest systems, resulting in global outbreaks. Global pathogen genomics data including population genomics and high-quality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 219 publications
2
22
0
Order By: Relevance
“…This study raises questions about the strategy for effectorinformed breeding. We know that clonal lineages predominate in strawberry, as has often been described in other agriculturalassociated pathosystems (Hessenauer et al, 2021). We have shown that there are highly expressed lineage-specific effectors within the clonal lineage of CR along with CNV in highly expressed effectors.…”
Section: Discussionsupporting
confidence: 62%
“…This study raises questions about the strategy for effectorinformed breeding. We know that clonal lineages predominate in strawberry, as has often been described in other agriculturalassociated pathosystems (Hessenauer et al, 2021). We have shown that there are highly expressed lineage-specific effectors within the clonal lineage of CR along with CNV in highly expressed effectors.…”
Section: Discussionsupporting
confidence: 62%
“…This study raises questions about the strategy for effector-informed breeding. We know that clonal lineages predominate in strawberry, as has often been described in other agricultural-associated pathosystems (Hessenauer et al, 2021). We have shown that there are highly expressed lineagespecific effectors within the clonal lineage of CR along with CNV in highly expressed effectors.…”
Section: Resultssupporting
confidence: 62%
“…The loss of sexual reproduction, caused by demographic events or selection against sex, is a frequent change in the life history traits of invasive fungal pathogens (Gladieux et al 2015;Hessenauer et al 2021). However, the underlying changes and driving factors remain largely unexplored.…”
Section: Pestification Can Foster Lineage Divergencementioning
confidence: 99%